Pelatihan Desain Grafis Dan Konten Kreatif Islami Sebagai Sarana Dakwah Digital Di As-Sittu Pandeglang - Romi Andrianto; Muhamad Arief Yulianto; Khairudin (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The development of social media has transformed communication patterns and Islamic preaching (da'wah) in the digital era. However, students of As-Sittu Islamic Boarding School in Pandeglang still have limited skills in graphic design and the creation of Islamic digital content. In addition, the utilization of the school's social media platforms for da'wah and publication purposes has not been fully optimized. The Islamic Graphic Design and Creative Content Training Program aims to enhance students' abilities in producing engaging digital da'wah content that aligns with Islamic values. The program includes training in the use of Canva and CapCut, the creation of da'wah posters and videos, social media management, and digital communication ethics. The methods employed consist of lectures, hands-on practice, and mentoring sessions. The expected outcomes are improved student competencies, the establishment of a creative team within the Islamic boarding school, and the production of Islamic creative content that supports digital da'wah and strengthens the institution's presence in the community.